Opening the Blackbox: How Does Labor Market Policy Affect the Job Seekers' Behavior? A Field Experiment - Patrick Arni (Institute for the Study of Labor (IZA), 2015)
Empirically, not much is known about the mechanisms how labor market programs like job search assistance and training operate to support finding a job. This paper provides novel evidence to open the "blackbox": it causally links the program interventions to the dynamics of search behavior, beliefs and non-cognitive skills. The study is based on a unique combination of a randomized field experiment with detailed register data and a panel of repeated surveys. The tested coaching program, focused on older job seekers, turns out to increase the job finding of participants by 9 percentage points (72% vs. 63% in the control group). The treatment effect is driven by a reduction of reservation wages and an increase in search efficiency. Moreover, I find short-run effects on motivation, self-confidence and beliefs. The job seekers overestimate their chances slightly less with respect to job interviews and salaries. Overall, the focus on realistic expectations and on search strategy appears to be important for program success. The experiment shows that evaluation designs which directly assess behavior can provide a fruitful base for targeted policy design.
Keywords: J64; J65; J68; J14; 330; field experiment; labor market policy; older workers; reservation wages; job search behavior; non-cognitive skills; biased beliefs; dynamic treatment effects; unemployment insurance